The Large Hellenic Study of Uveitis: Diagnostic and Therapeutic Algorithms, Complications, and Final Outcome. Issue 1 (2nd January 2023) - Kalogeropoulos, Dimitrios; Asproudis, Ioannis; Stefaniotou, Maria; Moschos, Marilita M.; Kozobolis, Vassilios P.; Voulgari, Paraskevi V.; Katsanos, Andreas; Gartzonika, Constantina; Kalogeropoulos, Chris
Abstract : Purpose: The purpose of this study is to present the diagnostic and therapeutic algorithms, complications, and final outcome in the management of uveitic patients at a tertiary academic referral center. Design: Observational study. Methods: Analysis of the archives of 6191 uveitic patients at the Ocular Inflammation Service of the Department of Ophthalmology of the University Hospital of Ioannina in Greece from 1991 to 2020. Results: During the 30 years of the study, the diagnostic ability climbed from 45.43% (1991–1995) to 73.4% (2016–2020). This improvement was linked to several factors including the increase in the number of diagnostic paracenteses for the analysis of intraocular fluids, the range and quality of laboratory blood tests, the multimodal ophthalmic imaging, the proper use of nonophthalmic imaging, and the multidisciplinary approach. The degree of uveitis-related complications was related to the severity and cause of inflammation, the recurrence rate, inappropriate treatment, and the prolonged or initially inactive inflammation. The 3 most common complications included cataract, macular edema, and glaucoma. Apart from the modern treatments and surgical techniques, the 3-month preoperative control of inflammation played a critical role in the surgical outcomes. The percentage of patients with a successful outcome increased from 72% (2001–2005) to 90.50% (2016–2020). The center's experience, prompt referral, patient's compliance, and regular follow-ups are associated with a better outcome. The analysis of the results allowed the development of diagnostic and therapeutic algorithms. Conclusions: Developing diagnostic and therapeutic algorithms allows for the efficient management of uveitis, leading to better visual outcome and therefore a better quality of life.